Comparative Analysis Of The Efficiency Of Auxiliary Power Unit (APU) And Ground Support Equipment (GSE) On The Electrical System Of Airbus A320 Aircraft - Ardiansyah, Luvan; Siagian, Parlin; Gunawan, Haris (Jurnal Media Computer Science, 2026)
This research analyzes the efficiency comparison between the Auxiliary Power Unit (APU) and Ground Power Unit (GPU) on the Airbus A320 aircraft's electrical system during ground operations. Aircraft operations require a stable power supply, provided by either an internal APU or an external GPU. Although the APU offers flexibility, its high fuel consumption and significant environmental impact are considerable concerns. Conversely, the GPU is deemed more efficient and environmentally friendly. The study aims to calculate energy consumption, analyze efficiency, and recommend the most efficient and environmentally sound electrical power source. The method employed is a quasi-experimental field observation, involving direct data collection from a Houchin LTD model C690 GPU unit. Data collection was conducted over 7 days, from June 1 to June 7, 2025. Data analysis includes mathematical calculations for energy efficiency and operational economic analysis. Research findings indicate that the GPU significantly outperforms the APU. The diesel GPU exhibits an energy efficiency of approximately 31.30%, considerably higher than the APU's around 1.54% (based on 7 days of data). The GPU also presents superior electrical power quality, characterized by a higher Power Factor and lower Total Harmonic Distortion (THD). It is recommended that airlines prioritize GPU usage, and airport authorities expand Fixed Electrical Ground Power (FEGP) infrastructure to enhance energy efficiency and reduce operational costs.